Adaptive Reconfigurable FBMC System for IoT Wireless Network - Sandeep Shrivastava, Alok Jain, Ram kumar Soni (International Journal of Advanced Science and Technology, 2020)
Internet of Thing (IoT) wireless system involves machine type of communication with a diversified application with different Quality of Service (QoS) demand and devices with different communication capabilities. The communication waveform design for such kind of heterogeneous network must be scalable and more adaptive. Filter bank multicarrier system offers less inter-carrier interference, which is one of the suitable waveforms to allocate required subcarrier for IoT devices. Filter-Bank Multiple carrier technique has developed as better alternative compared with OFDM in the field of wireless communication network. Coefficients of prototype filter used for the designing of Filter-Bank Multiple Carrier play a vital role in the designing of wireless network. The versatile need of wireless equipment in daily life is increasing exponentially. Now a single wireless network handles multiple types of devices in one bandwidth. Therefore in coming years the flexibility in distribution of bandwidth will be the prime feature of wireless network. Analysis of different parameters of IOT devices available in a single wireless network will give the better distribution of it among the devices.  This work focus on a genetic algorithm-based adaptive parameter selection of Filter-Bank Multiple carrier (FBMC) waveform to allocate bandwidth, subcarrier, carrier, and prototype filter (i.e. PHYDYAS, RRC and Hermite) to ensure the QoS demand of the IoT applications. The proposed mechanism is tested in three different applications.